Religious Educators: A Psychological Study of Qur’anic Verses Regarding al-Rahmah - Idi Warsah (Institut Agama Islam Negeri (IAIN) Curup, 2020)
This study applied a library research to explore and understand in-depth information as regards the essence of al-rahmah in Qur’anic verses as well as to integrate the concepts of al-rahmah with educational psychology concepts using a normative qualitative approach by analyzing the meanings of al-rahmah repeated 338 times in the Qur'an. The present study made efforts to find new concepts, especially on ideal educators’ personalities. Very contrary to the conclusion drawn by Amaechi stating that Islam provides both the ideological framework and the network platform upon which violent elements develop, the current study concluded that educators who have the characteristics of al-rahmah are those who have three religious personalities such as rabbany, nabawy, and insany that are bound by a strong belief in the power of Allah, observe the Islamic law well, and are fully aware that Allah always oversees their activities. With the aforesaid personalities, good educators are also associated with having high spirituality and religiosity (fearing of Allah and having noble characters), having good competences, extensive knowledge as well as being intelligent, being future-oriented, communicative (conveying knowledge with patience, sincerity, and with understandable methods), open to critic, authoritative, fair, non-discriminatory, and pleasant, and having polite speech